Do genérico ao gênero: as experiências masculinas como ponto de partida para o fazer teológico - Souza, Ezequiel de (2009)
This dissertation presents the transformations which provided the rise of the study field of manliness, result of transformations which happened in society and academy and were started by the feminist movement. With the access of women to different spheres of society, the masculine superiority was affected, generating the crisis of model of traditional manliness. The fissures in traditional manliness had evidenced the existence of alternative manliness. Glances on manliness since an interdisciplinary perspective allow us to identify three models of interpretation of manliness. They are models built since the analysis perspective and not since the specific content of researches. We also identified three appealing dimensions in the readings. Although they are complementally, they were separated in order to provide a more detailed vision on each dimension. The studies about manliness center its attention in sexual signs of masculine identity, relating the other dimensions to the phallus centrism and the libido dominandi. Finally, it systematizes the way as theology has been working with manliness, in order to identify which is the role that the experience occupies in theological studies.